2012
DOI: 10.1073/pnas.1120587109
|View full text |Cite
|
Sign up to set email alerts
|

Soluble factors produced by activated CD4+T cells modulate EBV latency

Abstract: Following infection with Epstein-Barr virus (EBV), the virus is carried for life in the memory B-cell compartment in a silent state (latency I/0). These cells do not resemble the proliferating lymphoblastoid cells (LCLs) (latency III) that are generated after infection. It is of fundamental significance to identify how the different EBV expression patterns are established in the latently infected cell. In view of the prompt activatability of CD4 + T cells in primary EBV infection, and their role in B-cell diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 25 publications
1
45
1
Order By: Relevance
“…Early studies have shown that IFN-g can limit, but not abolish, transformation of B cells (41,42), and recently this was proposed to occur through delayed upregulation of latent membrane protein-1 (16). IFN-g levels in cultures on day 14 were negatively correlated to the percentage of B cells after infection, suggesting that this cytokine (along with other aspects of T cell activation) (43) was involved in the inhibition of EBV expansion observed in the older age groups. In accordance with previous studies (13)(14)(15)(16)19), both T and NK cells were active and produced IFN-g, although intracellular staining revealed little in terms of which cell type was the main contributor to the secreted IFN-g.…”
Section: Discussionmentioning
confidence: 95%
“…Early studies have shown that IFN-g can limit, but not abolish, transformation of B cells (41,42), and recently this was proposed to occur through delayed upregulation of latent membrane protein-1 (16). IFN-g levels in cultures on day 14 were negatively correlated to the percentage of B cells after infection, suggesting that this cytokine (along with other aspects of T cell activation) (43) was involved in the inhibition of EBV expansion observed in the older age groups. In accordance with previous studies (13)(14)(15)(16)19), both T and NK cells were active and produced IFN-g, although intracellular staining revealed little in terms of which cell type was the main contributor to the secreted IFN-g.…”
Section: Discussionmentioning
confidence: 95%
“…ϩ T cells induce a switch from latency III toward latency IIa, and this is mediated, at least in part, by IL-21 and soluble CD40L (31).…”
mentioning
confidence: 99%
“…This suggests that sericin might have an effect on the function of cytotoxic T cells but it may not affect helper T cells. Despite the essential role of CD8 cell in anti-viral immunity, CD4 T cells can also play important roles for control of viral infection as well as cancer 26,27 . There was a reduction of CD80 positive cells without changes in CD86 positive cells.…”
Section: Discussionmentioning
confidence: 99%